Does Economics Need Psychology? - Špecián, Petr (Teorie vědy / Theory of Science, 2015)
The study shows a contrast between the Beckerian economic approach and behavioral economics. The methodological comparison of both alternatives is emphasized as well as the assessment of behavioral economics’ potential to cause a paradigm shift in economic thinking. I argue that behavioral economics was unable to offer a theoretical alternative to homo economicus so far. Also, its potential to overcome the rational choice theory in the long run predictive success that is the standard benchmark for theory evaluation in economics may be limited.